Examining Microbial Decomposition, Carbon Cycling and Storage in Cefni Coastal Salt Marsh, Anglesey Island, Wales, United Kingdom - Dasat, G. S.; Christopher, F.; Tim, J.; Dunn, C. (European Journal of Applied Sciences, 2024)
Salt marshes sequester carbon dioxide from the atmosphere into the soil, however, anthropogenic activities could release centuries of buried carbon dioxide, a major greenhouse gas implicated with climate change. Therefore, this study investigated biogeochemical activities in soil samples from low, mid and high zones of Cefni salt marsh, within the Maltreat estuary, on the island of Anglesey, north Wales, United Kingdom for a consortium of laboratory experiments using standard operating protocols to quantify soil organic matter contents and the rate of microbial decomposition and carbon storage. Results of investigations reveals that the mid zone had 56.23% and 9.98% of soil water and soil organic matter contents respectively higher than the low and high zones. Phenol oxidase activity (1193.53µmol dicq g-1 h-1) was highest at the low zone compared to the high and mid zones (867.60 and 608.74 µmol dicq g-1 h-1) respectively. Soil phenolic concentration was highest in the mid zone (53.25 µg-1 g-1) compared with high (15.66 µg-1 g-1) and low (4.18 µg-1 g-1) zones respectively. Activities of hydrolases showed similar trend for the high and low zones and much lower activities in the mid zone. CO2 flux from the mid zone (6.79 ug g-1 h-1) was significantly greater than those from high (-2.29 ug g-1 h-1) and low (1.30 µg g-1 h-1) zones. Since salt marshes provide essential ecosystem services, their degradation or alteration in whatever form could compromise vital ecosystem services, converting them from net sinks into net sources with consequential effects to the global environment.